Development of VBA for assessment of practical allowable pile capacity / Mohamad Irwan P. Harahap and Muhammad Safwan Mohd Sobri (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
The needs for computer-aided tools for fast and accurate engineering computing are increasingly becoming indispensable in the ever-challenging construction industry as well as academia. In this regards, the technical demands and public expectations largely dictate the way the profession are tackled in modern Malaysia. However, these programs are often computationally opaque or complex, not customize to local contexts, expensive due to specialized target market, and potentially requiring hardware-software-specific environment. As an alternative, this paper proposed the use of Visual Basic for Application (VBA) with MS EXCEL as the parent platform and adopting analytical formulations readily familiar to Malaysian practitioners and academicians. The selection is based on the ubiquity of the said platform and established competency among users. The program developed involved determination of allowable pile capacity. Finally, the program was run and tested against a real world pile foundation problem based on geotechnical data borelog. The results were found to be in agreement with manual computational procedures, and thus confirming its veracity and applicability for the prescribed technical determination.